Immune-related gene IL17RA as a diagnostic marker in osteoporosis - Deng, Ya-Jun; Li, Zhi; Wang, Bo; Li, Jie; Ma, Jun; Xue, Xiong; Tian, Xin; Liu, Quan-Cheng; Zhang, Ying; Yuan, Bin (Frontiers in Genetics, 2023)
Objectives: Bone immune disorders are major contributors to osteoporosis development. This study aims to identify potential diagnostic markers and molecular targets for osteoporosis treatment from an immunological perspective.We downloaded dataset GSE56116 from the Gene Expression Omnibus (GEO) database, and identified differentially-expressed genes (DEGs) between normal and osteoporosis groups. Subsequently, differentially-expressed immune-related genes (DEIRGs) were identified, and a functional enrichment analysis was performed. A protein-protein interaction network was also constructed based on data from STRING database to identify hub genes. Following external validation using an additional dataset (GSE35959), effective biomarkers were confirmed using RT-qPCR and immunohistochemical (IHC) staining. ROC curves were constructed to validate the diagnostic values of the identified biomarkers. Finally, a ceRNA and a transcription factor network was constructed, and a Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analysis was performed to explore the biological functions of these diagnostic markers.In total, 307 and 31 DEGs and DEIRGs were identified, respectively. The enrichment analysis revealed that the DEIRGs are mainly associated with GO terms of positive regulation of MAPK cascade, granulocyte chemotaxis, and cytokine receptor. PPI network analysis revealed 10 hub genes: FGF8,